Filsafat Pendidikan sebagai Dasar Pembelajaran Bermakna dalam Kurikulum Tematik SD - Nur Widyasti Utami; Widia Utami; Wiwi Widyaningsih; Ricky Yoseptry; Hendri Abdul Qohar (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2025)
This study aims to analyze the application of educational philosophy as the foundation of meaningful learning within the Thematic Curriculum in elementary schools. Educational philosophy—particularly progressivism, constructivism, and humanism—serves as an essential basis for designing holistic, contextual, and student-centered learning. However, the implementation of thematic learning in schools often reveals a gap between the philosophical foundations of the curriculum and classroom learning practices. This research employs a qualitative approach with a case study design. Data were collected through classroom observations, in-depth interviews with teachers, and document analysis of lesson plans (RPP) and learning implementation. The findings indicate that teachers’ understanding of the philosophical foundations of the curriculum varies and tends to be technical in nature. Nevertheless, several philosophical values—such as learning by doing, contextual learning, and respect for students’ individuality—have emerged in practice, although not yet implemented consistently. The contribution of educational philosophy is reflected in the increased relevance of learning materials to real-life contexts, the development of learner autonomy, and the creation of more meaningful learning processes. This study emphasizes the importance of strengthening teachers’ philosophical understanding as a key factor in the successful implementation of the Thematic Curriculum and as an effort to build learning that liberates students intellectually, socially, and emotionally.